A química na EJA: ciência e ideologia - Silva, Alceu Júnior Paz da (2007)
The contemporary setting of huge unemployment and precarization of work has brought to Adult and Youth Education courses an imaginary that secondary education is fundamental for professional qualification and achievement of (better) jobs. The objective of this work is to problematize the Chemistry curriculum according to young and adults interests in order to qualify them to the world of work. For that purpose, we adopted Michael Apple s curriculum theory and some contributions of Gramsci s Marxist social theory as methodological and theoretical tools to investigate hegemonic aspects in which the curriculum is immersed. By analyzing the curriculum as a space of struggle for social hegemony, we conclude that is promising to explore the historical approach of the chemical knowledge as a mediator element of counterhegemonic educational practices